Fine-grained attribute update and outsourcing computing access control scheme in fog computing - Ruizhong DU; Peiwen YAN; Yan LIU (Tongxin xuebao)
To slove the problem that in the fog computing environment with comparatively high low latency demand, ciphertext policy attribute based encryption (CP-ABE) faced the problems of high encryption and decryption overhead and low efficiency of attribute update, an fine-grained attribute update and outsourcing computing access control scheme in fog computing was proposed.The unanimous consent control by modular addition technique was used to construct an access control tree, and the computing operations of ecryption and decryption were outsourced to fog nodes in order to reduce user encryption and decryption overhead.Combined with the re-encryption mechanism, a group key binary tree was established at the fog node to re-encrypt the ciphertext so that user attribute can be updated flexibly.The security analysis shows that the proposed scheme is safe under the decision bilinear Diffie-Hellman hypothesis.Compared with other schemes, the results of simulation experiment prove that the time cost of user encryption and decryption in this scheme is lower and the efficiency of attribute update is higher.